2013
DOI: 10.1242/dev.089136
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for Pax6 in the segmental organization of the hindbrain

Abstract: SUMMARYComplex patterns and networks of genes coordinate rhombomeric identities, hindbrain segmentation and neuronal differentiation and are responsible for later brainstem functions. Pax6 is a highly conserved transcription factor crucial for neuronal development, yet little is known regarding its early roles during hindbrain segmentation. We show that Pax6 expression is highly dynamic in rhombomeres, suggesting an early function in the hindbrain. Utilization of multiple gain-and loss-of-function approaches i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 94 publications
(106 reference statements)
2
21
0
1
Order By: Relevance
“…1A, Figs. 2 and 3; Additional file 1) [15,34,43,72,73]. Notably, DAPI-negative gaps are present in the mantle-most layer of boundaries, which reflect nuclei-free domains (Additional file 1), consistent with previously published data [14][15][16].…”
Section: Sox2 Converges From the Entire Hindbrain To Its Boundaries Wsupporting
confidence: 86%
See 2 more Smart Citations
“…1A, Figs. 2 and 3; Additional file 1) [15,34,43,72,73]. Notably, DAPI-negative gaps are present in the mantle-most layer of boundaries, which reflect nuclei-free domains (Additional file 1), consistent with previously published data [14][15][16].…”
Section: Sox2 Converges From the Entire Hindbrain To Its Boundaries Wsupporting
confidence: 86%
“…All these proteins are known to be co-expressed with Sox2 in different NSCs [48-50, 61, 77-80]. Notably, Pax6 was previously found to be enriched at chick HBs [15,72]. Immunostaining of embryos revealed the co-localization of these markers with Sox2 within HBs ( Fig.…”
Section: Sox2 Is Expressed With Other Neural Progenitor Markers In Hbsmentioning
confidence: 88%
See 1 more Smart Citation
“…Although the r6/r7 interface is a bona fide lineage restriction (Fraser et al, 1990; Birgbauer and Fraser, 1994), we showed that it is less straight and displays less pronounced apical remodelling than other interfaces. This correlates, in the chick, with weaker Fgf3 and Pax6 expression at r6/r7 than at the Krox20 boundaries and manipulations of either gene at early somite stages can alter segmentation and boundary gene expression (Marín and Charnay, 2000; Weisinger et al, 2012; Kayam et al, 2013). However, when we ectopically expressed Pax6 or Fgf3 (or inhibited Fgf signalling) at the later developmental stage used in our Hox electroporations, apical remodelling at rhombomere boundaries was not detectably altered (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been suggested that Pax6 is involved in the specification of subtypes of hindbrain neurons (Osumi et al, 1997) and is currently determined as crucial factor in the segmental organization of the early hindbrain (Kayam et al, 2013). …”
Section: Discussionmentioning
confidence: 99%